2017
DOI: 10.1063/1.4983565
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional photonic confinement in imprinted liquid crystalline pillar microcavities

Abstract: We demonstrate the feasibility of a thermal imprint technology capable of structuring organic thin films with liquid crystalline properties forming feature sizes on a several micrometer scale. The imprint technique can directly be applied onto a variety of substrates including dielectric mirrors. The so fabricated three-dimensional microcavities have lateral extensions up to 20 µm and heights between 1 and 5 µm. Exemplarily, pillar microcavities were produced wherein three-dimensional photonic confinement is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The twist in the PBI cores and the steric demand of the dendrons play a key role in the columnar assembly modes, which in turn have an impact on the exciton couplings between dyes and on spectroscopic properties such as absorption and emission maxima of the J-aggregates. These results are of great importance for the fine-tuning of properties of tailor-made materials for photonic applications as it was recently demonstrated for MEH-PBI in imprinted LC pillar microcavities 39 .
Fig.
…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The twist in the PBI cores and the steric demand of the dendrons play a key role in the columnar assembly modes, which in turn have an impact on the exciton couplings between dyes and on spectroscopic properties such as absorption and emission maxima of the J-aggregates. These results are of great importance for the fine-tuning of properties of tailor-made materials for photonic applications as it was recently demonstrated for MEH-PBI in imprinted LC pillar microcavities 39 .
Fig.
…”
Section: Introductionmentioning
confidence: 60%
“…In this vein, we recently reported an unprecedented organization of PBIs into LC triple-stranded helical columnar structures in which the PBI cores are oriented parallel to the columnar axis 38 . This material was subsequently utilized in photonic microcavities 39 . Our molecular design consists of a tetra-bay functionalized MEH-PBI with 1,2-ethylhexyl (EH) substituents and free NH groups at the imide positions.…”
Section: Introductionmentioning
confidence: 99%
“…Using near‐field optical imaging techniques, it was shown that such structures were able to modify spontaneous emission rates. Organic micropillars have also previously been fabricated using a thermal imprint technology to pattern a liquid‐crystalline molecular dye into pillar shapes on the surface of a dielectric mirror . By coating such structures with a thin film of gold, the hemispherical pillar‐geometry cavities created were shown to support several families of quantized optical modes.…”
Section: Introductionmentioning
confidence: 99%
“…PBI J-aggregates are ideal candidates because they not only fulfill this essential criterion but also show hyperchromicity and fluorescence in the solid state . Accordingly, J-aggregates of PBIs 3d and 6d could be implemented in all-polymer photonic microcavities, pillar microcavities, and open microcavities . For the former, a film of PBI 3d J-aggregates in amorphous polypropylene (aPP) was prepared between two polymerically distributed Bragg reflectors (DBR) to afford a 5-fold increase in photoluminescence intensity compared to that of a reference sample and a narrow fwhm of 6.7 nm at the cavity mode wavelength (725 nm) (Figure , bottom right) …”
Section: Physical Properties and Application Of Pbi J-aggregatesmentioning
confidence: 99%